Prediksi Perilaku Siswa SMK N 2 Surakarta Menggunakan Metode Naive Bayes - Shalihah, Rahmania, Yusuf Sulistyo Nugroho., S.T., M.Eng (2016)
Public school as a means of accommodating diverse backgrounds of students with different personalities. With a background of a different personality may allow students to experience a variety of problems. Bad behavior is an issue that should be the concern of teachers today. Students with bad behavior require special attention from the school authorities which served to help solve the problems of the students. Moreover, it makes the performance of school will be delayed and disrupted. It can even reduce public confidence in the quality of the school. So, we need a system predictor of students is potentially create problems using Naive Bayes that will be nurtured and mentored by the school. Data mining technique that are used in predicting these students is Naive Bayes method. Naïve Bayes used to predict that the student could potentially create a problem or not, the variables used are the Department, IQ scores, emotional stability values, the value of social relationships and the value of self-confidence. Results from this study is an application system that can help the school in predicting and minimizing potential students make trouble.